In Silico Approach in Bioremediation - Singh, P.K.; Imam, J.; Shukla, P.
Interdisciplinary investigation of processes involved in bioremediation is latest drift toward finding novel ways and schemes to improve the conventional treatment of toxic compounds with microorganisms. Though microorganisms are being genetically modified to increase their efficiency, but time and funds are always remains matter of concern when it comes to implement idea in a larger picture. In silico methods, include different mathematical models, modeling of metabolism, genomics, proteomics and biodegradation pathways which are being implemented in the bioremediation process for effectual outcome. Role of biological databases in building mathematical model for bioremediation. Role of docking process in the screening of best interaction of pollutant and its enzyme which degrades it. It reduces the samples to be tested in wet lab. © 2014 Elsevier Inc. All rights reserved.
Keywords: BIODEGRADATION PATHWAYS; MATHEMATICAL MODELS; METABOLISM MODELING; MOLECULAR DOCKING; PATHWAY DATABASE